Perancangan Sistem Antrian Pasien Di Puskesmas XYZ Banjarmasin - Persadha, Galih; Anshari, Muhammad Rashif (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2024)
XYZ Health Center in Banjarmasin is a growing healthcare facility that currently uses a conventional queuing system. This system often encounters challenges, such as lost or damaged queue cards, manual queue calling by staff, and limited information about the current queue number. These issues make the queuing process less efficient. This study aimed to design a web-based patient queuing system at XYZ Health Center in Banjarmasin using a priority service method, developed with PHP programming language and a MySQL database. The research resulted in a web application with both back-end and front-end functionalities. The queuing system offers options for general and priority patients, with queue calls managed through the back-end according to patient categories. By implementing this application, the challenges associated with the conventional queuing system can be resolved, ensuring a smoother queuing process. The application has been tested by end users and deemed “suitable for use.” To maintain security, confidentiality, and optimal functionality, regular backups and proper network system configuration are required.